2016
DOI: 10.1039/c6ra02109c
|View full text |Cite
|
Sign up to set email alerts
|

A simple synthesis of sulfur-doped graphene using sulfur powder by chemical vapor deposition

Abstract: S-doped graphene has synthesized by CVD, using Fe/CaCO3 as a catalyst, acetylene as a carbon resource and sulfur powder as a sulfur resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Recently, various methods have been used in the synthesis of S‐doped graphene. Sulfur atoms can be inserted into the graphene frameworks using CVD and thermal annealing of GO . The sulfur‐containing porous carbon material has been synthesized using infiltration of the carbon source into zeolite pores by means of impregnation and CVD approach .…”
Section: Heteroatom‐doped Graphenementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, various methods have been used in the synthesis of S‐doped graphene. Sulfur atoms can be inserted into the graphene frameworks using CVD and thermal annealing of GO . The sulfur‐containing porous carbon material has been synthesized using infiltration of the carbon source into zeolite pores by means of impregnation and CVD approach .…”
Section: Heteroatom‐doped Graphenementioning
confidence: 99%
“…Since then, different liquid organic material precursors such as hexane have been also employed in the presence of sulfur when CVD method is used together with copper substrate . Hassani et al reported a high sulfur doping level of 5% (XPS) that was grown from CVD and sulfur powder as sulfur precursor. Thus, the level of sulfur in S‐doped graphene varies with synthetic technique and sulfur‐containing precursor used.…”
Section: Heteroatom‐doped Graphenementioning
confidence: 99%
See 1 more Smart Citation
“…Growing doped graphene in one step is also possible for instance by using CVD. For example, doping with nitrogen, boron, sulfur, phosphorus and silicon atoms has thus far been demonstrated by CVD. Among them, nitrogen is often a natural choice as a dopant due to its comparable size to carbon while it hosts an additional valence electron.…”
Section: D: Doped and Undoped Graphenementioning
confidence: 99%
“…Experimental works on the doping of graphene with P and S atoms have also been performed [13,14]. Density functional theory (DFT) calculations on the adsorption of several gas molecules on P-doped graphene (hereafter abbreviated as PhG) have shown strong chemisorption of O2, NO, NO2 and SO2 onto PhG through the formation of P-X (X = O, N, S) bonds, while weak physisorption was observed for H2, H2O, CO2, CO, N2 and NH3 [15].…”
Section: Introductionmentioning
confidence: 99%